Optimization of composite microbial agents containing plant inter-root growth-promoting bacteria and verification using mini Chinese cabbage (Brassica rapa L. ssp. Pekinensis) - Fan, Xiangjun; Yao, Wenxia; Liu, Taotao; Wang, Yan; Lu, Yang; Yang, Hongyu; Zhang, Yuxin (Frontiers in Plant Science, 2025)
Microbial agent research has developed from single strain to multi-strain complex studies, and Plant growth promoting rhizobacteria (PGPR) has emerged as a hot topic in relation to biofertilizers. Soil environmental degradation problems, such as soil compaction and fertility decline in the Hexi region of Gansu, China, are the focus of this study. The enrichment of PGPR resources and the elucidation of the plant growth-promoting effects of the PGPR strains are also investigated. This study isolated 26-PGPR strains from plant inter-root soils with phosphorous solubilizing ability, 15 strains with nitrogen fixing ability, and 7 strains with IAA secretion ability. The identified strains were from the genera Pantoea, Enterobacteriaceae, Acidovorax, Brucella, Ochrobactru, Achromobacter, Acinetobacte, and Alcaligenes. Six dominant strains were selected based on the identified characteristics to prepare composite microbial agents, which were then optimized using a pot experiment with mini Chinese cabbage (Brassica rapa L. ssp. Pekinensis) and the cross-crossing method. The TE (JQ-MY-41+JQ-MY-42+YC-342) treatment significantly promoted plant growth, and chlorophyll a and carotenoids were increased by 23.1% and 21.2% compared with the CK., respectively. With the TB treatment, Pn increased by 60.5%. The Fv/Fm, ETR, and leaf SOD and POD activities were significantly increased with the TE treatment compared with the TB treatment. Endogenous hormones, such as TZR, GA, and ABA, were significantly increased in TB- and TE-treated plants compared with the CK. Furthermore, organic matter and quick-acting potassium were increased by 33.4% and 71.3%, respectively, and alkaline nitrogen and quick-acting phosphorus were both 2.98 times higher with the TE treatment than with the CK. The correlation analysis of the indicators showed that for the composite mini-Chinese cabbage, TE is the optimal formula, and this will help guide future research and development into microbial fertilizers.